Integrasi Nilai-Nilai Rumah Tangga Kristen dalam Kurikulum Pendidikan Agama Kristen untuk Pembentukan Karakter Kristus di Era Digital - Kezia Verena; Evi Sondag; Chanita Christie Lohy; Yeyen Darmadi; Lidiawati Lidiawati (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2026)
The rapid growth of the digital era has significantly influenced Christian Religious Education (CRE), requiring curriculum transformation that integrates Christian household values into academic learning. This study employs a descriptive qualitative approach with an exploratory case study design to analyze the integration of family-based Christian values, such as love, open communication, and spiritual discipline, into the CRE curriculum. The findings reveal that this integration effectively nurtures Christlike character in students across cognitive, affective, and spiritual dimensions. In addition, technology-enhanced learning becomes more meaningful when it is rooted in household values that shape daily faith practices and relational responsibility. The study also indicates that the family context provides an important foundation for strengthening moral awareness, spiritual maturity, and responsible digital engagement among students. This research concludes that integrative curriculum models can develop educators who are not only theologically competent but also Christlike, adaptive, and responsive to digital challenges. Therefore, integrating Christian household values into CRE curriculum design is essential for strengthening holistic faith formation in higher education and preparing future educators to serve faithfully in contemporary digital contexts.